Strengthening Africa’s climate resilient outcomes: Policy coherence in climate-smart agriculture - Chevallier, Romy; Chesterman, Sabrina (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The recommendations in this policy briefing aim to enhance the design, financing, implementation and monitoring of CSA policies throughout Africa. Improving the coherence and alignment of CSA policies is key to achieving integrated and sustainable climate change, agriculture and food systems outcomes, as well as collectively catalysing the desired transformation of climate resilient agricultural production and robust food systems needed to support the continent’s development goals. In addition, policy integration is a requirement for coherent financing of CSA across the continent.